NUTRIENT AND STEROID CONTENTS OF SOME DEEP SEA FISH SPESIES FROM WESTERN SUMATERA, EASTERN INDIAN OCEAN - Sugeng Hari Suseno; Ali Suman; Wudianto Wudianto; Arin Damayanti (Indonesian Fisheries Research Journal, 2007)
The purpose of this research is to observe the content of nutrient and steroid of some deep sea fish from western Sumatera of the IndianOcean. A number of 11 fish species was examired in this work.